KR12 peptide-modified ECM coating for enhanced osteogenic and antimicrobial activity of titanium surfaces - Demirci, Emine Afra; Onder, Sakip; Acar, Tayfun; Sunar, Selin Zeynep; Kose, Gamze Torun (ELSEVIER, 2026)
Titanium (Ti)-based biomaterials are widely used in orthopedic and dental implants; however, their clinical success remains limited due to poor osseointegration and implant-associated infections. In this study, a functional surface modification strategy was developed by immobilizing the antimicrobial peptide KR12 via a collagen-binding peptide (CBP) onto decellularized extracellular matrix (ECM) coatings derived from cell sheet engineering. The ECM was obtained through a gentle decellularization process that preserved its native architecture and essential components, including collagen and fibronectin. KR12 was successfully anchored onto the ECM surface through CBP, ensuring antibacterial activity without disrupting ECM structure. Surface characterization using SEM, AFM, and XPS confirmed the morphological and chemical modifications associated with ECM deposition and KR12 immobilization. Antimicrobial assays demonstrated that while ECM alone exhibited no antibacterial effect, the addition of KR12 significantly reduced Staphylococcus aureus adhesion by up to 96 %. Cell studies revealed enhanced adhesion and proliferation on ECM-coated surfaces, and osteogenic assays confirmed that KR12-functionalized ECM coatings promoted early differentiation, with elevated ALP activity and increased expression of osteogenic genes such as ALP, Runx2, Col1a1, and OCN. This approach offers a promising strategy for improving implant performance by simultaneously promoting bone integration and providing long-term antibacterial protection.
Keywords: Cell Sheet Engineering; ECM Coating; Antimicrobial peptide; Collagen Binding Peptide; Osteogenic Differentiation; KR-12 PEPTIDE; IN-VITRO; CELL; DIFFERENTIATION; IMPLANTS; MATRICES; GROWTH; Materials Science